Codependent reintegration : research, rehabilitation and live in care facility - Homer, David Craig (My University, 2016)
Contrary to the general assumption, people with disabilities both physical and mental are just like you or me. We all come with our own set of limitations; the only difference is that their limitations affect the way they move, think, and experience life. Unfortunately, these characteristics are also used to discriminate against them and isolate them from society. South Africa uses SANS 10400 part S to ensure that architects enable people with disabilities to access and use the buildings they design. Although the regulation is largely focused on physical disabilities, there is reference to people with mental disabilities, however many institutions do not fulfil all the SANS requirements. (Homer,S 2016) Communities which are unable to care sufficiently for people with mental disabilities often place them into institutions where trained professionals aid, teach and enable them. These institutions are often cold, sterile and overcrowded. These institutes become their homes, and many residents view these centres as a place for some independence. Due to lack of funding and little to no opportunity to generate income for them, the residents continue to rely on their families to contribute to their income and items which aid their level of comfort. Several residents are not as fortunate and rely solely on trivial government grants. Through the redesign of a community centre for people with intellectual development disorders in a small town, this thesis will explore: • how architecture may affect the social integration of residents within a centre and between the residents and the community • How architecture can improve the ease at which people with disabilities live and experience life. • How architecture can assist in rehabilitation • The relationship between Institute and home in an attempt to break down the conventional institution and create a place for the mentally disabled where most would be comfortable.